Mu??af? al-Sib?’?’s Views on the Dynamics of Hadith: Ideas and Discourse on Hadith Studies - Muhammad Rizky Romdonny; Agung Danarta (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
The various ways in which Muslim scholars have responded to the views of orientalist thinkers show their attention to hadith studies. This article examines Mustafa Siba'i ideas in his work al-Sunnah wa Maknatuh fii al-Tasyri' al-Islam. There are several focuses revealed in this article, namely his ideas on the sunnah which also answer statements from several figures (Abu Rayyah, Taufiq Sidqi, and Ahmad Amin); as well as revealing the discourse of hadith studies as a development of al-Siba'i ideas. This research uses qualitative analysis with library research sources. It is known that the importance of historical analysis in knowing the context and continuity of the sanad (sanad criticism), and the importance of scientific integration in revealing the truth of a hadith (matan criticism). Therefore, it does not stop at understanding the idea, so it is necessary to develop the idea, in this case it can be found the discourse of hadith studies such as the application of Mustafa Siba'i ma'anil hadis, and the study of hadith historiography in several fields (mustalah al-hadis science and rijal al-hadis science). The development of the hadith signals how much he contributed to the field of hadith.